Can Natural Polyphenols Help in Reducing Cytokine Storm in COVID-19 Patients? - Giovanna Giovinazzo; Carmela Gerardi; Caterina Uberti-Foppa; Lucia Lopalco (Molecules, 2020)
SARS-CoV-2 first emerged in China during late 2019 and rapidly spread all over the world. Alterations in the inflammatory cytokines pathway represent a strong signature during SARS-COV-2 infection and correlate with poor prognosis and severity of the illness. The hyper-activation of the immune system results in an acute severe systemic inflammatory response named cytokine release syndrome (CRS). No effective prophylactic or post-exposure treatments are available, although some anti-inflammatory compounds are currently in clinical trials. Studies of plant extracts and natural compounds show that polyphenols can play a beneficial role in the prevention and the progress of chronic diseases related to inflammation. The aim of this manuscript is to review the published background on the possible effectiveness of polyphenols to fight SARS-COV-2 infection, contributing to the reduction of inflammation. Here, some of the anti-inflammatory therapies are discussed and although great progress has been made though this year, there is no proven cytokine blocking agents for COVID currently used in clinical practice. In this regard, bioactive phytochemicals such as polyphenols may become promising tools to be used as adjuvants in the treatment of SARS-CoV-2 infection. Such nutrients, with anti-inflammatory and antioxidant properties, associated to classical anti-inflammatory drugs, could help in reducing the inflammation in patients with COVID-19.